Spatio-temporal Dynamics of Urban Expansion: A Case Study of Sandhikharka Municipality - Adhikari, MaDhu Sudan; Ghimire, Subash; Paudyal, Dev Raj; Karki, Dhruba (Geographical Journal of Nepal, 2026)
Understanding the effects of urbanization and creating sustainable planning strategies requires a thorough analysis of urban growth patterns at various spatial and temporal levels. The aim of this paper is to explore the pattern of urban growth and its social, economic, and environmental impacts at the municipal level. This study examines the spatiotemporal pattern of urban growth in Sandhikharka Municipality, Arghakhanchi District of Nepal, from 2000 to 2019. Urban expansion is readily apparent in nearly every urban center, including Sandhikharka. As one type of land use expands, it inevitably leads to a reduction in another. If forests, grasslands, and other wooded areas diminish due to urban growth, the adverse impact on the environment becomes evident. Similarly, the reduction of cultivated land to accommodate urban development directly affects food production and sovereignty. Encroaching upon riverbeds for urban expansion exposes the town to increase vulnerability to flooding hazards. Thus, analyzing changes in landcover and urban growth reveals various environmental, social, and economic implications. The methodological approach applied in this study involved analyzing three commonly used indicators: The Urban Spatial Expansion Index, the Urban Expansion Intensity Index, and the Urban Spatial Expansion Rate. Additionally, visual interpretation of land cover maps and graphs of their area was conducted for further analysis. This study found that the annual rate of urban expansion steadily increased from 2000 to 2019. The study revealed a consistent increase in forest cover whereas cropland cover significantly decreased. Most notably, the riverbed and cultivated land were predominately converted into built-up areas, whereas grassland, other wooded land, and cultivated land were changed into forest cover. This suggests that the urban expansion of Sandhikharka does not directly impact on landscape degradation and reflects effective community forestry governance, legal protection mechanisms. However, there is a serious concern regarding the increased risk of flooding and the adverse effects on food yield and, consequently, food sovereignty.